Synthesis and Protein Tyrosine Phosphatase 1B-Inhibitory Activity of Chalcones - Zhao, Fei; Zhao, Qing-Jie; Zhang, Da-Zhi; Jin, Yong-Sheng; Zhang, Wei (Asian Journal of Chemistry, 2011)
Protein tyrosine phosphatase 1B (PTP1B) is an effective target for the treatment of type 2 diabetes and obesity. So far less work has been conducted in the structure-activity relationship of the PTP1B inhibitory activity of chalcones. In this work, a library of 65 chalcones were synthesized and their preliminary PTP1B inhibitory activities in vitro were evaluated and reported. Among them, 27 compounds displayed good inhibitory activity on PTP1B and seven compounds showed excellent activity. These results indicate that chalcones could be used for the design of more potent PTP1B inhibitors.